2016
DOI: 10.1002/cdq.12060
|View full text |Cite
|
Sign up to set email alerts
|

Career Development of Chinese Canadian Professional Immigrants

Abstract: Chinese professional immigrants make up the 2nd largest visible minority group in Canada. Their successful resettlement in the host country is inextricably tied to the prosperity and success of the general Canadian society that depends heavily on its immigration practice for the country's development and growth. However, there is a dearth of literature and research on this particular population, especially in the areas of career development and vocational psychology based on the unique cultural context of Cana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 29 publications
3
13
1
Order By: Relevance
“…Seeking higher education, making career-related decisions, and striving for success were frequently viewed as collective rather than individual endeavors for participants. These findings were consistent with recent scholarly work in the career development literature (Chen & Ling, 2016; Ouyang, Jin, & Tien, 2016). The expectation of assisting family members financially may make navigating competing narratives about career more complex.…”
Section: Discussionsupporting
confidence: 91%
“…Seeking higher education, making career-related decisions, and striving for success were frequently viewed as collective rather than individual endeavors for participants. These findings were consistent with recent scholarly work in the career development literature (Chen & Ling, 2016; Ouyang, Jin, & Tien, 2016). The expectation of assisting family members financially may make navigating competing narratives about career more complex.…”
Section: Discussionsupporting
confidence: 91%
“…Conflicts in career beliefs and career choices and decisions are largely affecting career development of individuals in different collectivistic Chinese societies (Kwan, 2009). For Chinese populations in Western host societies such as the United States and Canada, because a relatively complete career service system is basically established, their major career barrier might be how to adapt at different levels, such as work environment, communities, schools, and families, with increasing language ability and improving social support (Chen & Hong, 2016;Leong & Tang, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The article by Leong and Tang (2016) reviews career barriers experienced by Chinese immigrants in the United States. Chen and Hong (2016) address career development of Chinese Canadian professional immigrants, who constitute the second largest visible minority group and make substantial contributions to national growth and development in Canada. The career barriers for Chinese immigrants include ethnic stereotypes, unintended consequences of the model minority myth, language, lack of social support, and workplace discrimination.…”
Section: Content Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies in the fields of work and vocational psychology have identified some contextual and personal barriers to the career construction and professional integration of immigrants or refugees (Atitsogbe et al, 2019;Yakushko et al, 2008;Zacher, 2019). Among these contextual barriers, authors have stressed the nonrecognition of formal qualifications or work experiences, the refugees' or asylum seekers' lack of work permits, discrimination, and poor networks (Chen & Hong, 2016).…”
Section: Barriers-and Resources-to Professional Integrationmentioning
confidence: 99%